Le World Press Photo ou le photojournalisme au Salon - Lavoie, Vincent (Ciel variable)

(untitled) (Les Productions Ciel variable, 2006)
The World Press Photo grand prize, one of the most important distinctions awarded in the photojournalism field, has been handed out every year since 1955 to the person who makes the image that is most exemplary of a recent current event. These images, true icons of contemporary history, are shown in annual exhibitions presented simultaneously in a number of major world capitals. The "masterpieces" of the news media are symbols of merit and artistic accomplishment, objects of reward and recognition. This article advances the hypothesis that rhetorics of excellence and coronation constitute strategic valorizations of photojournalism in a situation of economic and aesthetic crisis.